Analisis Sentimen Global terhadap Volatilitas Realisasi Investasi Asing di Indonesia: Komparasi Struktural dan Guncangan Institusional Awal 2026 - Fauzan Zidane Alhakim; Gilang Nurul Hakim; Muhammad Taqi Fadhillah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze Indonesia's macroeconomic anomaly in early 2026, where a surge in real sector investment realization was inversely proportional to extreme volatility in the capital market. Using a qualitative descriptive approach with secondary data triangulation, this research dissects global sentiment through the lens of economic institutionalism theory and event analysis. The results indicate that the record investment of IDR 1,931.2 trillion at the end of 2025 was dominated by Foreign Direct Investment (FDI) in the mineral downstream sector, which is categorized as sunk-cost assets, thus having low mobility against bureaucratic risks. Conversely, Foreign Portfolio Investment (FPI) showed a hyper-sensitive reaction to institutional transparency deficits, triggering a capital outflow of IDR 6.24 trillion following the MSCI index moratorium and Moody’s Ratings outlook downgrade. Regional comparison shows that Vietnam is superior in attracting high-tech investment due to regulatory efficiency and stronger global supply chain integration. This study concludes that abundant natural resources are insufficient to guarantee economic stability without institutional integrity and accountable legal certainty.